2023
DOI: 10.1101/2023.08.30.555493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological modeling of SARS-CoV-2 in white-tailed deer (Odocoileus virginianus) reveals conditions for introduction and widespread transmission

Elias Rosenblatt,
Jonathan D. Cook,
Graziella V. DiRenzo
et al.

Abstract: Emerging infectious diseases with zoonotic potential often have complex socioecological dynamics and limited ecological data, requiring integration of epidemiological modeling with surveillance. Although our understanding of SARS-CoV-2 has advanced considerably since its detection in late 2019, the factors influencing its introduction and transmission in wildlife hosts, particularly white-tailed deer (Odocoileus virginianus), remain poorly understood. We use a Susceptible-Infected-Recovered-Susceptible epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…For wild deer, the same panel estimated that suburban settings had 2.7 times higher proximity rates when compared to rural and ranch (captive) deer 9 (Supplementary Table 3). Despite these differences, Rosenblatt et al (2023) 8 found that simulated disease outcomes had low sensitivity across the range of human-to-deer spillover rates, suggesting that infrequent human-to-deer transmission events are sufficient to initiate sustained outbreaks in deer. Deer-to-deer transmission, however, was sensitive to parameter values.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For wild deer, the same panel estimated that suburban settings had 2.7 times higher proximity rates when compared to rural and ranch (captive) deer 9 (Supplementary Table 3). Despite these differences, Rosenblatt et al (2023) 8 found that simulated disease outcomes had low sensitivity across the range of human-to-deer spillover rates, suggesting that infrequent human-to-deer transmission events are sufficient to initiate sustained outbreaks in deer. Deer-to-deer transmission, however, was sensitive to parameter values.…”
Section: Discussionmentioning
confidence: 99%
“…Deer are assumed to be evenly distributed with all individuals subjected to the same contact rates. We parameterized the model to simulate the midwestern U.S. during the fall season (September-December; 120-day window) when humans may contact deer during hunting and other activities and acquired parameter estimates using empirical data and expert elicitation 8 (Supplementary Table 3).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations